Address to the U.N. Economic and Social Council - McNamara, Robert S. (World Bank, Washington, DC, 2020)
Robert S. McNamara, President of the World Bank Group, discussed two issues: the operations of the Bank, both for the past fiscal year and for the period covered by the Five-year Program, and the relationship of the Bank to the rest of the U.N. system. The Five- Year Program was developed with the objective of doubling the Bank Group's operations from 1969-1973, as compared with 1964-1968. Two years into the Program, the interim objectives are being met. Economic progress remains precarious and sterile without corresponding social improvement; the Bank intends to give attention to both.